ELECTROSTATIC CATALYSIS OF OXIDATION REACTIONS BY METAL-CATIONS - AN ABINITIO STUDY - Clark, Timothy; et al. (Journal of the American Chemical Society, 1991)
UMP4SDTQ/6-31G*//6-31G* calculations indicate that complexation of the oxidant with alkali metal cations provides both a strong catalysis of the forward reaction and a thermodynamic stabilization of the products in hydrogen atom abstraction reactions of triplet dioxygen and the hydroperoxy radical with methane, which was used as a model carbon-centered hydrogen atom donor. This effect, which is expected to be general for metal monocations, is based on purely electrostatic interactions, as is shown by the dependence of the calculated activation and reaction energies on the ionic radius of the metal and on the polarization of the O-3(2) and by model calculations using only 1 s orbital as the basis set for Li+.